Partial AUCs in Long-Acting Injectables: Rationale, Challenges, Variability, Usefulness, and Clinical Relevance - Georgia Tsakiridou; Maria-Faidra-Galini Angelerou; Panagiotis Efentakis; Antonios Margaritis; Antigoni-Maria Papanastasiou; Lida Kalantzi (Pharmaceutics)
Regulatory authorities typically require bioequivalence to be demonstrated by comparing pharmacokinetic parameters like area under the plasma concentration-time curve (AUC) and maximum plasma concentration (Cmax). Because in certain cases, AUC and Cmax alone may not be adequate to identify formulation differences in early and/or late segments of the dosing interval, partial AUCs (pAUCs) have been proposed as additional metrics to evaluate bioequivalence. Even though cut-off points for pAUCs are usually decided based on clinical relevance, the identification of the correct cut-off range remains elusive in many other cases and tends to contribute to increased pAUC estimate variabilities. The choice of meaningful cut-off points in pAUC estimates can be especially difficult in the case of long-acting injectable (LAI) products, where long dosing intervals and complex pharmacokinetic (PK) and pharmacodynamic (PD) profiles apply, but most importantly, because there is not always a clear PK/PD relationship established. In this communication, authors discuss the usefulness and challenges associated with the estimation of pAUCs in the development of generic LAI products through the review of six case studies under the lens of regulatory requirements from the two major authorities, namely the FDA and EMA.